PENINGKATAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN KOLASE DI TK SANTA MARIA SINTANG - Sudarto, Sudarto; Sarayati, Sarayati (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe the creativity of children aged 5–6 years through collage activities at TK Santa Maria. The research employed a descriptive qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which includes planning, action, observation, and reflection stages. The subjects consisted of 15 children. Data were collected through observation, interviews, and documentation, using observation sheets, interview guides, and documentation records. Data analysis followed the stages of data reduction, data display, and verification (conclusion drawing). The results showed an improvement in children’s creativity across cycles. The average score of students’ activity in Cycle I was 57.10, which increased to 73.40 in Cycle II. This improvement was reflected in the achievement indicators of children’s fine motor skills. In addition, teacher activity also improved, with an average score of 53.20 in Cycle I (categorized as fairly good) and increasing significantly to 92% in Cycle II. In conclusion, collage activities effectively enhance creativity and fine motor skills in early childhood, as well as improve teacher performance in the learning process.